Integrating computational thinking into English writing: development of a computational thinking-integrated module - Saad, Aslina; Hashim, Haslinda; Rahmatullah, Bahbibi (Journal of Education and Learning (EduLearn), 2026)
This study addresses challenges in teaching English writing skills in English as a second language (ESL) classrooms, proposing a novel approach through computational thinking (CT). A CT-integrated writing module was developed for primary school ESL teachers using the analysis, design, development, implementation, and evaluation (ADDIE) model and qualitative research. Incorporating constructivist and experiential learning theories, the module uses visualization tools like circle maps and flow maps across 8 units, combined with an inquiry-based approach, scaffolding, and localized materials. The 5 CT elements-decomposition, pattern recognition, abstraction, algorithmic thinking and logical reasoning-are embedded to enhance learning. Focus group interviews with 4 ESL experts indicate strong acceptance, highlighting the module’s usability, content, and teaching activities. The study provides a framework for CT-based instructional modules to improve problem-solving and cooperative learning in English writing education.